Avaliação dos Efeitos de Tratamentos Silviculturais em Florestas Secundárias de Diferentes Estágios Sucessionais no Município de Bragança, Pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2007)
Secondary vegetation is the main form of land use in the Northeast of Pará. The diversity of products, timber and non-timber, potentially commercial offered by "capoeiras" makes them amenable to management. The objective of this work is to study the effects of silvicultural treatments on the diametric increment of secondary forest species of socioeconomic interest to farmers. The management of secondary forests with the application of silvicultural treatments, aiming to increase production, is an alternative for their conservation and to generate additional income for farmers in the Bragantine region. The treatments were defined as follows: TO (witness plot) and Ti (plot with silvicultural intervention). The silvicultural interventions consisted of tree felling (thick trees) and thinning: vine cutting and direct felling (thin trees) carried out in two stands intended for diversified production, called Agricultural Units (I and II). For the treated plots of LAU I, the species with the highest values of Annual Periodic Increment (API) were Rheedia acuminata (Ruiz & Pav.) Planch. & Triana (bacuri-pari), Eugenia tapacumensis O. Berg (jabuti food) and Croton matourensis Aubl. (maravuvuia) with average of 0.85,0045,0040 in year 1, respectively. However, interventions in Agrarian Unit II caused larger increments in the species Stryphnodendron guianensis (Aubl.) Benth (Paricazinho), Byrsonima guianensis (Muruci vermelho) and Buchenavia amazônica Alwan & Stace (Tanimbuca), with averages of 1.05, 0.9, 0.9 cm.eno'. respectively. The average IPA for the group of individuals benefited by the silvicultural treatments in LAU I and LAU II were 0.33 and 0.37 cm.eno', respectively. While for the group of control individuals it was 0.28 and 0.29 cm.year', respectively. The results of this study infer that forest management with the application of silvicultural treatments is feasible for secondary forests by favoring the development of its species, especially the diametric increment.
Evaluation of the Effects of Silvicultural Treatments in Secondary Forests of Different Successional Stages in the Municipality of Bragança, Pará
Keywords: Vegetação secundária; Manejo florestal; Intervenção silvicultural.; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::FITOGEOGRAFIA